Comparison of the finishing shot and ending zone of points in Grand Slam matches of women`s doubles tennis: A cross-sectional study - Borderias, M.; Iglesias, X.; Martínez-Gallego, R.; Baiget, E. (PLOS ONE, 2024)
Despite the importance of doubles tennis, there is little research on this modality of the game, especially in women`s tennis. The aim of this study was to analyse the finishing shot, the ending zone and shot by ending zone of women´s doubles matches during three Grand Slams (GS), and to observe the differences among surfaces. Twenty-one women`s doubles matches from three GS, each played on a different surface were analysed. 56.4 ± 2.3% of the points were finished from the baseline and mid court zone (BMZ), 36.1 ± 2.3% from the net zone (NZ) and 7.5 ± 4.2% from the service zone (SZ). The shot with which the points ended primarily was the forehand volley (FV) (18.2 ± 3.5%), followed by the forehand (F) (17.4 ± 4.2%), the backhand (B) (15.8 ± 4.8%), the backhand volley (BV) (12.8 ± 3.6%), the forehand return (FRT) (11.7 ± 2.7%), the backhand return (BRT) (11.4 ± 2.6%), the service (S) (7.5 ± 4.2%) and the overhead (O) (5.2 ± 3.0%). The results showed a higher percentage of F played from the BMZ in Roland Garros (RG) than in Wimbledon (W) (p = 0.011). In addition, the results also showed a higher percentage in overall F in RG than in W (p = 0.023). The FRT percentage was higher in the Australian Open (AUS) compared to RG (p = 0.026), and the O shots played from the BMZ were higher in W than RG (p = 0.038). These results suggest that in professional women`s doubles tennis the net game is a determinant factor, as well as the volley (V) and F shots. Playing aggressive and close to the net may have a positive effect on the result.